2012
DOI: 10.1057/dddmp.2012.25
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the diffusion of marketing messages across a social network

Abstract: The last few years have seen signifi cant investment in social media as an adver sing, marke ng and customer outreach opportunity. In the US alone, in 2010, almost $ 1.7 bn was spent by adver sers on social media marke ng, with 53 per cent specifi cally allocated to Facebook 1 . Due to the explicit links that users maintain with each other, social media pla orms are perceived as a highly suited environment for network-based marke ng: word-of-mouth marke ng, diff usion of innova on, or buzz and viral marke ng 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…However, not all posts will be shared by cascading. Empirical research on Facebook did not show evidence of cascading as such, but rather the colliding of shorter chains while a threshold amount of start-nodes were needed in order to spread apost wider (Rogers et al, 2012).…”
Section: Cascadingmentioning
confidence: 95%
See 2 more Smart Citations
“…However, not all posts will be shared by cascading. Empirical research on Facebook did not show evidence of cascading as such, but rather the colliding of shorter chains while a threshold amount of start-nodes were needed in order to spread apost wider (Rogers et al, 2012).…”
Section: Cascadingmentioning
confidence: 95%
“…Facebook in turn facilitates active involvement with friends, e.g. through 'likes' that strengthenrelationships (Rogers et al, 2012). The use of "likes" has also been used in campaigns to create weak ties.…”
Section: Social Media Have Various Features That Enable Fast Disseminmentioning
confidence: 99%
See 1 more Smart Citation
“…Cascading refers to a message being passed to a first group of receivers who in turn pass it on to the next, igniting further explosions of information. Simple cascading has been contested in studies that have pointed to the existence of thresholds and have suggested that the widening diffusion of information would be better explained as triggered by a collision of shorter chains of communication (Rogers et al, 2012). This line of thinking has also led to studies investigating the role of weak Zhang, B., Vos, M. and Veijalainen (in press, 2017), Decomposing issue patterns in crisis communication -The case of the lost airliner.…”
Section: Understanding Issue Spread In the Social Mediamentioning
confidence: 99%
“…Cascading refers to a message being passed to a first group of receivers who in turn pass it on to the next, igniting further explosions of information. Simple cascading has been contested in studies that have pointed to the existence of thresholds and have suggested that the widening diffusion of information would be better explained as triggered by a collision of shorter chains of communication (Rogers et al, 2012). This line of thinking has also led to studies investigating the role of weak links in passing messages on to other groups of users (Zhao et al, 2010).…”
Section: Understanding Issue Spread In the Social Mediamentioning
confidence: 99%